PENDAMPINGAN UMKM DALAM PENGGUNAAN DIGITAL MARKETING PADA PELAKU UMKM DI DESA SUMUR, KECAMATAN BRANGSONG, KABUPATEN KENDAL - Abdullah Abdullah; Tri Sumiyanti; Emi Wardati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service activity aimed to provide assistance to Micro, Small, and Medium Enterprises (MSMEs) in Sumur Village, Kendal Regency, in utilizing digital marketing to support business development. The program focused on helping participants establish and manage online stores through social media platforms. Conducted from May 19 to May 30, 2025, the activity involved five groups of micro and medium-scale MSME actors. The training materials covered product photography and videography techniques, business logo design, and guidelines for creating and managing online stores via social media. The entire program was carried out successfully, with a 100% attendance rate in every session. Additionally, participants were given access to recorded training sessions to support independent learning. This initiative is expected to enhance the digital competencies of MSME actors and improve their market reach and business competitiveness.